Lifetime versus 10-year risk of recurrent events in patients with cardiovascular disease: impact of age. (11th May 2022) - Van Trier, T; Snaterse, M; Hageman, SHJ; Hoeve, N; Sunamura, M; Moll Van Charante, EP; Galenkamp, H; Deckers, JW; Visseren, FLJ; Scholte Op Reimer, WJM; Peters, RJG; Jorstad, HT
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Most risk models for patients with established atherosclerotic cardiovascular disease (ASCVD) calculate short-term risk of recurrent events and death, typically for a duration of 10 years. However, lifetime risk estimates may better support the healthcare professional in selecting patients for intensified preventive treatment (1). Also, a cross-sectional study suggested that communicating lifetime risk to ASCVD patients enhances risk perception and willingness for therapy (2). In the new ESC prevention guideline, however, 10-year risk estimates remain standard for ASCVD patients but the additional use of lifetime risk is recommended for communication in the shared decision-making process (3). Purpose: We therefore aimed to compare estimates of 10-year with lifetime risk of recurrent ASCVD events or death, stratified by age. Methods: We pooled individual-level data on risk factors from six large, recent prospective studies (RESPONSE 1 and 2, OPTICARE, EUROASPIRE IV and V and HELIUS). We included Dutch patients aged ≥45 years with a follow-up of ≥6 months after acute coronary syndrome or revascularisation. The SMART-REACH models were used to estimate the difference between 10-year and lifetime risk of recurrent myocardial infarction, stroke, or cardiovascular death, stratified by age (<55, 55-65, 65-75, ≥75 years). Results: In 3, 230 ASCVD patients (24% women), mean age 61±8 years, at median follow-up 1.1 (IQR 1.0-1.8) years after index event, SMART-REACH 10-year risk was 23±11% versus lifetime 56±11%. (Figure 1) We found a considerable difference between 10-year and lifetime risk in patients aged 45-55 years (18±8% vs. 61±10%). Discrepancies decreased with increasing age, with similar estimates in the highest (75-85) age group. (Figure 2). Conclusion: Lifetime risk of a limited set of cardiovascular outcomes rather than 10-year risk may provide a more complete estimate of future ASCVD disease burden, as especially in younger patients 10-year risk is usually low, even in the presence of risk factors.